Effect of temperature on the corrosion behavior of mild steel upon exposure to palm biodiesel - Fazal, M.A.; Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan (2011)
Recently biodiesel, as an alternative fuel is getting more significance to replace diesel fuel completely or partially. However, corrosion of automotive materials in biodiesel is a major concern as this can reduce engine life. This study aims to investigate the corrosion behavior of mild steel at three different temperatures such as room temperature, 50 and 80 degrees C. Static immersion tests in B0 (diesel), B50 (50 biodiesel in diesel), B100 (biodiesel) were carried out for 1200 h. At the end of the tests, corrosion characteristic was investigated by weight loss measurements and changes of the exposed metal surface. Fuels were analyzed by using TAN analyzer and Fourier transform infrared spectroscopy (FTIR) in order to investigate the change in acidity and oxidation of fuel respectively upon exposure. Surface morphology was examined by optical microscope and scanning electron microscope equipped with energy dispersive spectroscopy. Corrosion products were detected by X-ray diffraction (XRD). Results showed that the corrosion of mild steel increases with increase of temperature. Upon exposure of biodiesel to mild steel at high temperature, the water content and oxidation products are increased. (C) 2011 Elsevier Ltd. All rights reserved.